PENGARUH UMUR PERUSAHAAN DAN KOMITE AUDIT TERHADAP AUDIT REPORT LAG DENGAN REPUTASI KAP SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR TRANSPORTASI DI BURSA EFEK INDONESIA TAHUN 2018-2022) - Finna; Purwasih, Desy (Publika Citra Media, 2024)
This research aims to determine and obtain empirical evidence of the influence of company age and audit committee on audit report lag, with reputation as a moderating variable in transportation sector service companies listed on the IDX in2018-2022. This type of research is quantitative research and uses secondary data in the form of audited annual financial reports sourced from the official website of the Indonesia Stock Exchange (BEI). The population in this research istransportation sector service companies registered on the BEI in 2018-2022 with 15 companies as the population, and the sample technique used was purposive sampling and 13 companies were sampled within 5 years of observation. The data analysis technique in this research uses logistic regression analysis in the Eviews 9 software application. The results of this research simultaneously show that company age and the audit committee have an effect on audit report lag and partially show that company age has no effect on audit report lag while the audit committee has an effect. against Audit Report Lag, and also Kap's reputation cannot moderate the age of the Company and the audit committee against audit report lag.